2016
DOI: 10.1039/c5cy02125a
|View full text |Cite
|
Sign up to set email alerts
|

Role of different coordinated Cu and reactive oxygen species on the highly active Cu–Ce–Zr mixed oxides in NH3-SCO: a combined in situ EPR and O2-TPD approach

Abstract: Novel Cu–Ce–Zr mixed oxides were synthesized by a citric acid sol–gel method, and they exhibited an excellent NH3-SCO activity (180 °C, TOF = 1.33 h−1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 64 publications
(59 reference statements)
0
34
0
2
Order By: Relevance
“…For the CuTiO x catalyst, two types of isolated Cu 2+ ions characterized by the four hyperfine splitting lines overlap the broad signal with two different values for parallel components of g // (H 1 ) = 2.43 and g // (H 2 ) = 2.33, which have A // (H 1 ) = 78 G and A // (H 2 ) = 192 G, respectively. The value for the g-tensor is the fingerprint of the Cu 2+ ions located at an axially distorted octahedron, indicating the existence of Cu 2+ occupying the Ti 4+ sites in the TiO 2 lattice . The component having two different resonance parameters, g // (H 1 ) = 2.43 and g // (H 2 ) = 2.33, with a perpendicular parameter, g ⊥ = 2.06, can be assigned to Cu 2+ ions at substitutional cation sites of TiO 2 with different coordination numbers. , Similar signals corresponding to the formation of Cu 2+ ions in substituted octahedral sites with a tetragonal distortion have also been observed upon Cu 2+ incorporated ZrO 2 and TiO 2 surfaces. , The spectra feature of the CuO/TiO 2 catalyst evidence the only existing form of the CuO nanoparticle since no other isolated Cu 2+ ion induced anisotropic hyperfine structures were detected.…”
Section: Resultsmentioning
confidence: 98%
“…For the CuTiO x catalyst, two types of isolated Cu 2+ ions characterized by the four hyperfine splitting lines overlap the broad signal with two different values for parallel components of g // (H 1 ) = 2.43 and g // (H 2 ) = 2.33, which have A // (H 1 ) = 78 G and A // (H 2 ) = 192 G, respectively. The value for the g-tensor is the fingerprint of the Cu 2+ ions located at an axially distorted octahedron, indicating the existence of Cu 2+ occupying the Ti 4+ sites in the TiO 2 lattice . The component having two different resonance parameters, g // (H 1 ) = 2.43 and g // (H 2 ) = 2.33, with a perpendicular parameter, g ⊥ = 2.06, can be assigned to Cu 2+ ions at substitutional cation sites of TiO 2 with different coordination numbers. , Similar signals corresponding to the formation of Cu 2+ ions in substituted octahedral sites with a tetragonal distortion have also been observed upon Cu 2+ incorporated ZrO 2 and TiO 2 surfaces. , The spectra feature of the CuO/TiO 2 catalyst evidence the only existing form of the CuO nanoparticle since no other isolated Cu 2+ ion induced anisotropic hyperfine structures were detected.…”
Section: Resultsmentioning
confidence: 98%
“…Qu and Wang et al [317] prepared a series of Cu/CZO materials by the incipient-wetness impregnation, CA-SG, and homogeneous precipitation methods. Cu/CZO prepared by the CA-SG method exhibited the best NH3-SCO activity owing to its better adsorption capacity, more isolated Cu 2+ , and active oxygen adspecies.…”
Section: Effect Of Active Phase Types and Reaction Conditionmentioning
confidence: 99%
“…Qu and co-worker [317] proposed that the mechanism of NH3-SCO with lattice oxygen was different from that of gaseous oxygen, which was much less active than gaseous oxygen at low temperature. They suggested that the reaction mechanism of NH3-SCO over Ru/Ce0.6Zr0.4O2 should follow an internal SCR mechanism [319], as shown in Fig.…”
Section: Mechanisms Of Nh3 Oxidation Over Nanosize Ceria-zirconium-bamentioning
confidence: 99%
“…Moreover, with the addition of FeOx [40,41] or CoOx [42], the high-temperature activity can be enhanced. Some main group elements, such as Zr [43] and Sn [44], have commonly been used to modify CuO. Both these oxides have nearly no activity in catalytic reactions.…”
Section: Solid Solution Copper Oxides (Cuox-x)mentioning
confidence: 99%